THE INFLUENCE OF RISK PERCEPTION, FINANCIAL LITERACY, AND BEHAVIORAL MOTIVATION ON INVESTMENT DECISIONS OF INVESTORS AT PT. MIRAE ASSET SECURITIES INDONESIA GALLERY MEDAN - Januar Samuelson Gea; Syahyunan; Nisrul Irawati (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
This research aims to analyze the influence of risk perception, financial literacy, and behavioral motivation on investment decisions among investors at PT Mirae Asset Sekuritas Indonesia Galeri Medan. The research method employed is a causal associative study using a quantitative approach. The study population consists of 518 investors who have invested with PT Mirae Asset Sekuritas Indonesia Galeri Medan. The sampling technique used is nonprobability sampling via simple random sampling, resulting in 84 respondents as the research sample. Data collection was carried out by distributing questionnaires to the participants. The research findings indicate that simultaneously, the variables of risk perception, financial literacy, and behavioral motivation significantly influence investment decisions at PT Mirae Asset Sekuritas Indonesia Galeri Medan. Partially, risk perception has a non-significant negative effect on investment decisions at PT Mirae Asset Sekuritas Indonesia Galeri Medan, financial literacy has a significant positive influence on investment decisions at PT Mirae Asset Sekuritas Indonesia Galeri Medan, and behavioral motivation has a non-significant positive effect on investment decisions at PT Mirae Asset Sekuritas Indonesia Galeri Medan.